A Mística do Contestado: a mensagem de João Maria na experiência religiosa do Contestado e dos seus descedentes - Tomazi, Gilberto (2005)
The Contestado is one of the greatest popular movements and armed conflicts in the history of Brazil. It happened between 1912 to 1916 and embodied a region equivalent to one third of the Santa Catarina territory and the southwest of Parana. Not only the geographic amplitude and the long period of war but it is also remarkable the involvement of some tens of thousands of people with great number of deaths. The Contestado scarred and still influences the life, culture and religiousness of the ones who survived and their descendents. This dissertation studies and explains the Contestado mystics, from a symbolic-cultural perspective and from the current reception and new significance to João Maria s words. This mystical experience and its message still lives in various expressions and religious representations of the Contestado descendents. Retrieving them, from their origins to the present days, is the path walked by this dissertation. Around the Contestado and João Maria s message, several myths, rites, symbols, sacrifices and prayers have appeared, and are still kept in the popular memory of the Contestado descendents and reinterpreted in their religious experience. After almost a century, the Contestado itself has been given a new significance in a way that the cabocla community finds in it a sense, an inspiration and a mystical experience that allow them to live in the present in a sympathetic way, with esteem and acknowledgement, facing the harsh reality in which they find themselves, trusting in better days. After a revision and bibliographical analysis, retrieving historical, geo-political, social-economical and specially cultural and religious aspects of the Contestado, the most precious information in this dissertation were borrowed, from the people s popular testimonies, who keep alive the memory of the message and the mystics of João Maria. Thus, it was possible to trail a path for retrieval and valuing of the culture and the religious and popular experience of the Contestado.